The recording and reporting of floating ice - Armstrong, Terence (Polar Record, 1958)
The need to record and report the distribution of floating ice has arisen where-ever ships have been required to sail regularly in ice-filled waters. Various systems have been developed to meet the needs of particular areas, but these have grown up largely independently of each other. Such systems are generally designed to fulfil either, or both, of two purposes. One is the immediate end of providing material for a synoptic ice map, which is the basis of help to ships in the form of statements of the present whereabouts of the ice or predictions of its movements for a short period ahead. The other is a longer-term end, such as ice probability study, which seeks to utilize past records over as many years as possible in order to ascertain, in general terms, the probability of access to a given place at a given time; a result of such a study may be, for example, an ice atlas, of which two, covering wide areas, have appeared since the Second World War. Another long-term end is use of the ice pattern as an index of climatic change. Both lines of ice study require detailed information on the state of the ice, but each puts it to a different use. The problem, then, consists of devising a means of recording on paper, either photographically, cartographically, by means of explanatory text, or in some form of code convenient for radio transmission, the relevant facts about the distribution and behaviour of an area of floating ice, and also of reporting these in comprehensible terms, first to a collecting centre, and then to the users.